1979
DOI: 10.1103/physrevb.20.2886
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of the vanadium Magnéli phasesVnO2n1at low temperature

Abstract: The magnetic susceptibilities of the insulating Magneli phases V30~, V407, V60~~, and V80~& have been measured at low temperatures.Due to a short-range-order effect V305 exhibits a broad maximum at 125 K, which is substantially higher than the Neel temperature, 76 K, of this compound. For V407 and V60~~the difference between the Neel temperature and the temperature of the maximum in the susceptibility is small. This excludes the possibility that a linearchain model discussed by Khattak et al. can explain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…43 V 2Ϫy O 3 (yϷ0.03), on the other hand, sustains its high-T metallic state down to low temperatures, and at its Néel temperature T N ϳ10 K it undergoes a transition to an antiferromagnetic phase with a cusp in (T). 43 V 3 O 5 also orders antiferromagnetically at T N ϭ75.5 K, but (T) shows a broad maximum at a higher Tϭ125 K. 44 Though not detected in our x-ray diffraction measurements, V 4 O 7 , which has the same V oxidation state as in LiV 2 O 4 , also displays a cusp in obs (T) at T N Ϸ33 K and obs (T) follows the Curie-Weiss law for Tտ50 K. 44 The susceptibilities of these V-O phases are all on the order of 10 Ϫ4 -10 Ϫ3 cm 3 /mol at low T. 43,44 Moreover, the T variations of obs (T) in these vana-dium oxides for TՇ10 K are, upon decreasing T, decreasing (V 2Ϫy O 3 ) or nearly T independent (V 3 O 5 and V 4 O 7 ), in contrast to the increasing behavior of our Curie-like impurity susceptibilities. From the above discussion and the very small amounts of V-O impurity phases found from the Rietveld refinements of our x-ray diffraction measurements, we conclude that the V-O impurity phases cannot give rise to the observed Curie-like upturns in our obs (T) data at low T. These Curie-like terms therefore most likely arise from paramagnetic defects in the spinel phase and/or from a very small concentration of an unobserved impurity phase.…”
Section: Overview Of Observed Magnetic Susceptibilitymentioning
confidence: 89%
“…43 V 2Ϫy O 3 (yϷ0.03), on the other hand, sustains its high-T metallic state down to low temperatures, and at its Néel temperature T N ϳ10 K it undergoes a transition to an antiferromagnetic phase with a cusp in (T). 43 V 3 O 5 also orders antiferromagnetically at T N ϭ75.5 K, but (T) shows a broad maximum at a higher Tϭ125 K. 44 Though not detected in our x-ray diffraction measurements, V 4 O 7 , which has the same V oxidation state as in LiV 2 O 4 , also displays a cusp in obs (T) at T N Ϸ33 K and obs (T) follows the Curie-Weiss law for Tտ50 K. 44 The susceptibilities of these V-O phases are all on the order of 10 Ϫ4 -10 Ϫ3 cm 3 /mol at low T. 43,44 Moreover, the T variations of obs (T) in these vana-dium oxides for TՇ10 K are, upon decreasing T, decreasing (V 2Ϫy O 3 ) or nearly T independent (V 3 O 5 and V 4 O 7 ), in contrast to the increasing behavior of our Curie-like impurity susceptibilities. From the above discussion and the very small amounts of V-O impurity phases found from the Rietveld refinements of our x-ray diffraction measurements, we conclude that the V-O impurity phases cannot give rise to the observed Curie-like upturns in our obs (T) data at low T. These Curie-like terms therefore most likely arise from paramagnetic defects in the spinel phase and/or from a very small concentration of an unobserved impurity phase.…”
Section: Overview Of Observed Magnetic Susceptibilitymentioning
confidence: 89%
“…Kachi et al have reported on the magnetic susceptibility, and the insulator‐to‐metal transition, in these compounds . Maximal magnetic susceptibility was observed for these compounds near the corresponding Néel temperatures . The insulator‐to‐metal transition is coupled to an anomaly in the magnetic susceptibility without long‐range magnetic order .…”
Section: Structure‐composition‐properties Interplaymentioning
confidence: 98%
“…[96] Maximal magnetic susceptibility was observed for these compounds near the corresponding Néel temperatures. [97] The insulator-to-metal transition is coupled to an anomaly in the magnetic susceptibility without long-range magnetic order. [69,96,98] While the insulating phases are dominated by localized charges, itinerant and localized electrons coexist in the metallic phases.…”
Section: N O 2n-1mentioning
confidence: 99%
“…[253,262] References [263][264][265] [244, [266][267][268][269][270][271][272][273][274][275] [276] [276][277][278] [279] [280] [ [281][282][283][284][285][286] [180] [180] [ [286][287][288][289] [281] [283,[290][291][292] x except for a peak at low [309] temp. [253,262] References [263][264][265] [244, [266][267][268][269][270][271][272][273][274][275] [276] …”
Section: Rh02unclassified